INTEGRASIKAN HIGHER ORDER THINGKING SKILLS (HOTS) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (PEMBELAJARAN GURU SD MUHAMMADIYAH 2 SANGATTA UTARA) - Anjani Putri Belawati Pandiangan (Al-Rabwah, 2021)
Teachers in the learning process in the classroom are seen as being able to play an important role, especially in helping students to build positive attitudes in learning, arouse curiosity, encourage independence and accuracy of intellectual logic, and create conditions for success in learning. This study aims to determine the integration of HOTS in PAI and Budi Pekerti subjects, in this case, the learning of SD Muhammadiyah 2 North Sangatta teachers. This study uses a type of qualitative research field research (fields work research). This means that in this research, the researcher immediately jumps into the field to start research on the target object that has been determined in order to obtain data and information in accordance with what is needed in the study. The data collected is not in the form of numbers, but the data comes from the results of observations, interviews and documentation. There are research findings conducted by SD Muhammadiyah 2 Sangatta Utara teachers in the learning process based on higher Order Thinking Skills (HOTS), namely students are able to process, conceptualize and conclude in which students can solve problems by thinking creatively, critically, and able to argue in making decisions. a decision from the assignment given to the subjects of Islamic Religious Education and character in schools.